Generation of mature compact ventricular cardiomyocytes from human pluripotent stem cells. (3rd October 2022) - Funakoshi, S; Keller, G K
Abstract: Introduction: Compact cardiomyocytes that make up the ventricular wall of the adult heart represent an important therapeutic target population for modeling and treating cardiovascular diseases. Although human pluripotent stem cell (hPSC) represents a promising source to generate target cells in vitro, there has been no optimal protocols to generate mature compact cardiomyocytes derived from hPSCs. Purpose: To establish the protocol to generate mature compact ventricular cardiomyocytes derived from hPSCs. Methods: By mimicking the early ventricular development and postnatal maturation process observed in the heart in vivo, we searched for the specific factors to induce compact lineage and promote their maturation level. Results: We established a differentiation strategy that promotes the specification, proliferation and maturation of compact ventricular cardiomyocytes from hPSCs. The treatment of Wnt signaling activator, CHIR, and IGF2 significantly increased the expression level of a compact marker, MYCN (p=0.006), and suppressed the trabecular markers, NPPA (p=0.0117) and BMP10 (p=0.0032). Those factors induced a proliferation of compact cardiomyocytes by two folds (p<0.0001). Additionally, we identified that the combination of PPARα agonist, dexamethasone, T3 hormone, and palmitate in the low glucose containing media following the compact specification period significantly induced the fatty acid transporter, CD36, in the compact cardiomyocytes (p<0.0001). The CD36-positive compact cardiomyocytes generated under these conditions displayed the ability to use fatty acids as an energy source, a high mitochondrial mass, well-defined sarcomere structures and enhanced contraction force. These mature compact cardiomyocytes showed metabolic changes indicative of those associated with heart failure when challenged in vitro with pathological stimuli and were found to generate grafts consisting of more mature cells than those derived from immature cardiomyocytes following transplantation into infarcted rat hearts. Conclusions: We successfully generated the mature compact cardiomyocytes derived from hPSCs. These findings highlight the power of recapitulating key aspects of embryonic and postnatal development for generating therapeutically relevant cell types from hPSCs. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Canadian Institutes of Health Research (CIHR)